Produksi Desinfektan Dan Sanitizer Untuk Memutuskan Virus Corona Pada Masyarakat Di Kecamatan Pangkajene, Kabupaten Pangkep - Nur Fitriani Usdyana Attahmid; Muhammad Yusuf; Rahmawati Saleh; Syahriati Syahriati; A. Ridwan Makkulawu; Imran Muhtar (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
The training of disinfectants and sanitizers aims to help reduce the spread and break the chain of corona virus in the people of Pangkajene sub-district, Pangkep district. This is expected to increase entrepreneurial starting from innovation to create entrepreneurial independence. This program exchanging information and knowledge explore people's creativity. This training was carried several stages; providing material presented by online workshops and training people to innovate entrepreneurship. Methods of implementing activities based on inputs (a) survey, (b) feasibility study, (c) selection of materials; processes (a) model making, (b) online shop marketing; community creative output to be marketed. The results of this activity (1) to make easier for obtain products, (2) independent production becomes pilot innovation improving entrepreneurial skills and spirit to seize business opportunities, (3) online community entrepreneurship training improves the quality of independence business opportunities, (4) cultivating mindset for creatively innovative entrepreneurship using online shop business communication technology.